Major Impact of Sampling Methodology on Gene Expression in Estrogen Receptor–Positive Breast Cancer. Issue 2 (22nd May 2018) - Gao, Qiong; López-Knowles, Elena; U Cheang, Maggie Chon; Morden, James; Ribas, Ricardo; Sidhu, Kally; Evans, David; Martins, Vera; Dodson, Andrew; Skene, Anthony; Holcombe, Chris; Mallon, Elizabeth; et al.
Abstract: To investigate the impact of sampling methodology on gene expression data from primary estrogen receptor–positive (ER+) breast cancer biopsies, global gene expression was measured in core-cut biopsies at baseline and surgery from patients randomly assigned to receive either two weeks of presurgical aromatase inhibitor (AI; n = 157) or no presurgical treatment (n = 56). Those genes most markedly altered in the AI group (eg, FOS, DUSP1, RGS1, FOSB ) were similarly altered in the no treatment group; some widely investigated genes that were apparently unaffected in the AI group (eg, MYC ) were counter-altered in the control group, masking actual AI-dependent changes. In the absence of a control group, these artefactual changes would likely lead to the most affected genes being the erroneous focus of research. The findings are likely relevant to all archival collections of ER+ breast cancer.